Penerapan Kemampuan Metode Ekspositori untuk Meningkatkan Motivasi dan Kreativitas Siswa pada Mata Pelajaran Matematika - Darmawati Darmawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the activities of students towards the application of expository methods in mathematics learning as well as to find out directly the results of improved learning outcomes through the application of expository methods of numerical counting operations in class IV in Rejang Lebong Public Elementary School 13. This type of research is a classroom action research with the number of research subjects consisting of 12 male students and 18 people in 3 cycles. From the results of this study, the average score of the teacher observation cycle I is 13, Cycle II is 18, cycle III is 23. The average value of student observation cycle I is 13, cycle II is 17, cycle III is 20 with good categories . The results of learning completeness data in the cycle were 33.3% with an average value of 6.46. In cycle II the learning completeness was 50% with an average value of 6.7 increasing to 7.13. Conclusion, the expository method can increase students' motivation and creativity in mathematics. Keywords: Expository Method, Creativity, Learning Motivation